The Inventory of Bamboo in Antirogo Sub-district Sumbersari District Jember Regency - Ali Murtodo; Dwi Setyati (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2014)
Antirogo is a sub-district of Jember district, it's surrounding citizen utilize bamboo for daily needs such as building materials, agricultural equipment, bridges, vegetables and crafts. The continuous utilization is not accompanied by efforts of cultivating so that will have impacts on a population decline and preservation of them. Then it needs to do an inventory of bamboo in Antirogo. This research was conducted on March to September in 4 villages (Krajan, Trogowetan, Pelinggian, and Jambuan) used the exploration method. The results showed that 11 species of bamboo which consists of 4 genus (Bambusa, Dendrocalamus, Gigantochloa, and Schizostachyum) i.e. Bambusa blumeana Bl. ex Schult., Bambusa maculata Widjaja, Bambusa vulgaris Schard. ex J.C., Bambusa vulgaris var. striata (Lodd. ex Lindl.), Dendrocalamus asper Backer, Gigantochloa apus Kurz, Gigantochloa atter (Hassk.) Kurz ex Munro, Gigantochloa sp., Gigantochloa pseudoarundinacea (Steud.) Widjaja, Schizostachyum silicatum Widjaja, dan Schizostachyum zollingeri Steud. Keywords: Antirogo, Bamboo, Inventory, Poaceae.